2020
DOI: 10.1002/jcu.22891
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of a breath‐hold protocol to determine cerebrovascular reactivity in adolescents

Abstract: Purpose: Cerebrovascular reactivity (CVR) is impaired in adolescents with cardiovascular disease risk factors. A breath-hold test is a noninvasive method of assessing CVR, yet there are no reliability data of this outcome in youth. This study aimed to assess the reliability of a breath-hold protocol to measure CVR in adolescents. Methods: Twenty-one 13 to 15 year old adolescents visited the laboratory on two separate occasions, to assess the within-test, within-day and between-day reliability of a breath-hold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…When analysed in this way, the results of the current study demonstrated acceptable within-and between-day reliability (8.1-11.7%) using the MCAv peak response. This compares favourably to similar variables investigating cerebrovascular regulation via TCD using breath hold-induced CVR or as the percentage increase in MCAv without normalising to the P ETCO 2 stimulus (Koep et al, 2020;McDonnell et al, 2013). It therefore seems that expressed as an absolute CVR using the peak MCAv is the most reliable method to assess CVR.…”
Section: Traditional Cvr Analysesmentioning
confidence: 63%
“…When analysed in this way, the results of the current study demonstrated acceptable within-and between-day reliability (8.1-11.7%) using the MCAv peak response. This compares favourably to similar variables investigating cerebrovascular regulation via TCD using breath hold-induced CVR or as the percentage increase in MCAv without normalising to the P ETCO 2 stimulus (Koep et al, 2020;McDonnell et al, 2013). It therefore seems that expressed as an absolute CVR using the peak MCAv is the most reliable method to assess CVR.…”
Section: Traditional Cvr Analysesmentioning
confidence: 63%
“…Cerebrovascular reactivity to hypercapnia and hypocapnia was inferred using a repeated breath holding and separate hyperventilation protocol, respectively. Such an approach is advocated as an alternative to inhalation of higher concentrations of CO 2 ( 31 33 ), and we replicated a breath holding and hyperventilation protocol which is sensitive to alterations post concussion ( 34 ). Participants were coached to perform both techniques prior to any data collection, with particular instruction to avoid the Valsalva maneuver during breath holding.…”
Section: Methodsmentioning
confidence: 99%
“…10,100,101 The BHI values reported here are within the range of what is expected in a healthy young cohort but is higher than has been reported in some healthy cohorts. [102][103][104][105] The difference may be explained by the fact that some groups identify the maximum CBF at the moment the breath-hold ends, 41,106 which underestimates the BHI because the maximum CBF is expected to occur a few seconds after the completion of the breathhold. 100,106,107 Another consideration is the focus on a single breath-hold, rather than averaging multiple breath-holds as is performed by some groups.…”
Section: Discussionmentioning
confidence: 99%